2004
DOI: 10.1152/jn.00859.2003
|View full text |Cite
|
Sign up to set email alerts
|

GABA Neurotransmission in the Cerebellar Interposed Nuclei: Involvement in Classically Conditioned Eyeblinks and Neuronal Activity

Abstract: The cerebellar interposed nuclei (IN) are an essential part of circuits that control classically conditioned eyeblinks in the rabbit. The function of the IN is under the control of GABAergic projections from Purkinje cells of the cerebellar cortex. The exact involvement of cerebellar cortical input into the IN during eyeblink expression is not clear. While it is known that the application of gamma-aminobutyric acid-A (GABA(A)) agonists and antagonists affects the performance of classically conditioned eyeblink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
71
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 22 publications
12
71
1
Order By: Relevance
“…Indeed, it is known that during eyeblink conditioning many PCs learn to pause, completely suppressing their firing for hundreds of milliseconds during the generation of conditioned eyelid responses (Jirenhed et al, 2007). In addition, conditioning-related increases in the firing of DCN neurons are qualitatively similar in magnitude to the increases we measured during photostimulation (McCormick and Thompson, 1984;Aksenov et al, 2004;Chen and Evinger, 2006;Campolattaro et al, 2011). However, under normal learning conditions, DCN neurons may also be directly activated by new mossy fiber collaterals that could contribute to motor control by providing an additional excitatory drive beyond what is achieved by PC-mediated disinhibition alone Ohyama et al, 2006;Boele et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, it is known that during eyeblink conditioning many PCs learn to pause, completely suppressing their firing for hundreds of milliseconds during the generation of conditioned eyelid responses (Jirenhed et al, 2007). In addition, conditioning-related increases in the firing of DCN neurons are qualitatively similar in magnitude to the increases we measured during photostimulation (McCormick and Thompson, 1984;Aksenov et al, 2004;Chen and Evinger, 2006;Campolattaro et al, 2011). However, under normal learning conditions, DCN neurons may also be directly activated by new mossy fiber collaterals that could contribute to motor control by providing an additional excitatory drive beyond what is achieved by PC-mediated disinhibition alone Ohyama et al, 2006;Boele et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…The four rabbits in the IN recording group were also implanted with a microelectrode array/micromanipulator assembly targeting the left IN as in the study by Aksenov et al (2004). The manipulator contained three bundles of microwire electrodes totaling 14 electrodes (stainless steel, 18 m diameter, Formvar insulation).…”
Section: Surgerymentioning
confidence: 99%
“…The increased activity of these inhibitory cells then suppressed activity of IN neurons, as shown by our measurements. Because sustained inhibition of IN neurons suppresses CR expression (Aksenov et al, 2004), we presume that the NBQX-triggered tonic shifts in the activity of cerebellar neu- rons are either partly or completely responsible for the observed CR deficit. Interestingly, even though the NBQX-induced suppression of IN activity was sufficient to prevent CR expression, it was smaller than what we reported in DGG injection experiments (Zbarska et al, 2007).…”
Section: Involvement Of the Io In Expression Of Crs: Tonic Dysfunctiomentioning
confidence: 99%
“…Early results in rabbits ranged from complete abolition of the learned responses pointing to the cerebellar cortex as the key site (Yeo, 1991) to nominal effects that suggested a more fundamental role for the AIN (McCormick and Thompson, 1984). Numerous subsequent studies measuring closure of the external eyelid or nictitating membrane have reported responses with relatively fixed and short latencies to onset (ϳ80 -150 ms) after direct lesions (McCormick and Thompson, 1984;Perrett et al, 1993;Perrett and Mauk, 1995;Garcia et al, 1999;Medina et al, 2000) or infusing GABA A antagonists into the AIN (Garcia and Mauk, 1998;Medina et al, 2001;Ohyama and Mauk, 2001;Bao et al, 2002;Ohyama et al, 2003;Aksenov et al, 2004). We previously hypothesized that these short-latency responses (SLRs) (see Fig.…”
Section: Introductionmentioning
confidence: 99%